2002
DOI: 10.1097/00002030-200210180-00001
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of non-nucleoside reverse transcriptase inhibitor hypersusceptibility

Abstract: NNRTI hypersusceptibility occurred in more than 20% of nucleoside-experienced patients and was associated with greater reduction of HIV RNA and increase in CD4 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
41
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 2 publications
7
41
0
Order By: Relevance
“…The routine use of highly reproducible phenotypic assays (24) revealed that many clinical HIV-1 isolates exhibited significant hypersusceptibility (defined as a change in the 50% inhibitory concentration versus the reference of Յ0.4-fold) to the non-nucleoside reverse transcriptase inhibitor class (12,31,34). This phenomenon is associated with previous nucleoside analogue treatment and with an increase in the efficacy of salvage antiretroviral regimens including non-nucleoside reverse transcriptase inhibitors (12,31,32,34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The routine use of highly reproducible phenotypic assays (24) revealed that many clinical HIV-1 isolates exhibited significant hypersusceptibility (defined as a change in the 50% inhibitory concentration versus the reference of Յ0.4-fold) to the non-nucleoside reverse transcriptase inhibitor class (12,31,34). This phenomenon is associated with previous nucleoside analogue treatment and with an increase in the efficacy of salvage antiretroviral regimens including non-nucleoside reverse transcriptase inhibitors (12,31,32,34).…”
mentioning
confidence: 99%
“…This phenomenon is associated with previous nucleoside analogue treatment and with an increase in the efficacy of salvage antiretroviral regimens including non-nucleoside reverse transcriptase inhibitors (12,31,32,34). In chronically infected antiretroviral-experienced patients, amprenavir hypersusceptibility is associated with the N88S mutation in protease, which is not seen in drug-naïve patients (26,35).…”
mentioning
confidence: 99%
“…Hypersusceptibility (HS) to ARV drugs, defined here as susceptibility Յ0.4-fold that of HIV-1 NL4-3 , is another phenotype that was first described in the context of patients who had been treated with a failing ARV regimen; HS to nonnucleoside reverse transcriptase inhibitors has recently been shown to be clinically significant (4). In one study, among those who had acquired a virus strain resistant to nelfinavir, Ͼ6% were found to be HS to amprenavir (18).…”
Section: The Initial Virus Strains From As Many As 12% Of Individualsmentioning
confidence: 99%
“…Phenotypic hypersusceptibility of HIV-1, defined as having a greater than 2.5 fold increase in susceptibility to a drug compared with a wild-type reference strain using the phenotypic resistance assay by Monogram Biosciences (formerly ViroLogic), occurs with protease inhibitors and non-nucleoside reverse transcriptase inhibitors (NNRTIs) [17][18][19][20] . HIV-1 variants with phenotypic NNRTI hypersusceptibility are more likely to be resistant to nucleoside analogs 17,[20][21][22] . In patients, the presence of HIV-1 with NNRTIhypersusceptibility is associated with improved responses to an NNRTI-containing regimen compared to patients with variants that are not hypersusceptible 8,20,21,23 .…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 variants with phenotypic NNRTI hypersusceptibility are more likely to be resistant to nucleoside analogs 17,[20][21][22] . In patients, the presence of HIV-1 with NNRTIhypersusceptibility is associated with improved responses to an NNRTI-containing regimen compared to patients with variants that are not hypersusceptible 8,20,21,23 .…”
Section: Introductionmentioning
confidence: 99%